Hypermethylation of BRCA1 gene in meningioma in elderly males - Lombardi, Ismael Augusto Silva [UNESP]; Faria, Mário Henrique Girão; Rabenhorst, Silvia Helena Barem; Zanini, Marco Antônio [UNESP]; De Moura Campos Pardini, Maria Inês [UNESP]; Grotto, Rejane Maria Tommasini [UNESP]; Ferrasi, Adriana Camargo [UNESP] (Anticancer Research USA, 2018)
Background/Aim: Breast cancer 1, early onset (BRCA1) gene is expressed in the cells of the breast and other tissues, where it plays a role in cell-cycle regulation, transcription, repair of DNA double-stranded breaks, ubiquitination, transcriptional regulation as well as other functions, such as cell response regulation to mitogenic signals triggered by estrogens. Considering that meningioma shows greater tumor growth during pregnancy, can express estrogen receptors and proliferate in response to estrogenic stimulation, the hypothesis that this type of tumor may share molecular mechanisms that involve exposure to estrogen should be investigated. Therefore, the aim of the present study was to investigate the BRCA1 gene methylation profile in meningioma. Materials and Methods: Methylation-specific polymerase chain reaction (PCR) assay was performed on 50 meningioma samples from male and female patients. Statistical analysis was carried out using Fisher’s exact test. Results: The most important finding of this study was that 100% of the male patients over 55 years with meningioma showed BRCA1 methylated in their tumor cells. Conclusion: The silencing of BRCA1 through hypermethylation seems to play an important role in meningioma.
Keywords: BRCA1; Elderly males; Estrogens; Hypermethylation; Meningioma